Individual Consistency of Feather Pecking Behavior in Laying Hens: Once a Feather Pecker Always a Feather Pecker? - Daigle, Courtney L.; Rodenburg, T. Bas; Bolhuis, J. Elizabeth; Swanson, Janice C.; Siegford, Janice M. (Frontiers in Veterinary Science, 2015)
TThe pecking behavior (severe feather, gentle feather, and aggressive pecks) of individual White Shaver non-cage laying hens (n = 300) was examined at 21, 24, 27, 32, and 37 wk. Hens were housed in 30 groups of 10 hens each and on 3cm litter with access to a feeder, perch, and two nest boxes. The number of severe feather pecks given and received was used to categorize hens as feather peckers (P), victims (V), neutrals (N), or feather pecker-victims (PV) at each age. Hens categorized as PV exhibited pecking behaviors similar to P and received pecks similar to V. Severe feather pecks (SFP) given were correlated with aggressive pecks given, but not with gentle feather pecks given throughout the study. State transition plot maps illustrated that 22.5% of P remained P, while 44% of PV remained PV throughout the duration of the study. Lifetime behavioral categories identified hens as a consistent feather pecker (5%), consistent neutral (3.9%), consistent victim (7.9%), consistent feather pecker-victim (29.4%), or inconsistent (53.8%) in their behavioral patterns throughout their life. Consistent feather peckers performed more SFP than hens of other categories, and consistent neutral hens received fewer gentle feather pecks than consistent feather pecker-victims. No differences in corticosterone or whole blood serotonin levels were observed among the categories. Approximately half of the population was classified as a feather pecker at least once during the study, while the remainder was never categorized as a feather pecker. Therefore, even if the development and cause of feather pecking may be multi-factorial, once the behavior has been developed, some hens may persist in feather pecking. However, as some hens were observed to never receive or perform severe feather pecks, emphasis should be made to select for these hens in future breeding practices.